Efficacy of Sacrospinous Fixation or Uterosacral Ligament Suspension for Pelvic Organ Prolapse in Stages III and IV: Randomized Clinical Trial - Sérgio Brasileiro Martins; Rodrigo de Aquino Castro; Claudia Cristina Takano; Gisele Vissoci Marquini; Leticia Maria de Oliveira; Paulo Cezar Feldner Martins Junior; Márcia Maria Dias; Manoel João Batista Castello Girão; Marair Gracio Ferreira Sartori (Revista Brasileira de Ginecologia e Obstetrícia, 2023)
Abstract Objective To evaluate the efficacy and outcomes of the surgical treatment for pelvic organ prolapse (POP) in stages III and IV by sacrospinous ligament fixation (SSLF) or uterosacral ligament suspension (USLS) by comparing anatomical and subjective cure rates and quality-of-life parameters (through the version validated for the Portuguese language of the Prolapse Quality of Life [P-QoL] questionnaire) under two definitions: genital prolapse Ba, Bp, and C< −1 (stage I) and Ba, Bp, and C ≤ 0 (stage II). Materials and Methods After we obtained approval from the Ethics Committee (under CAAE 0833/06) and registered the study in ClinicalTrials.gov (NCT 01347021), 51 patients were randomized into two groups: the USLS group (N = 26) and the SSLF group (N = 25), with follow-up 6 and 12 months after the procedures. Results There was a significant improvement in the P-QoL score and anatomical measurements of all compartments in both groups after 12 months (p< 0.001). The anatomical cure rates in the USLS and SSLF groups, considering stage 1, were of 34.6% and 40% (anterior) respectively; of 100% both for groups (apical); and of 73.1% and 92% (posterior) respectively. The rates of adverse outcomes were of 42% (N = 11) and 36% (N = 11) for the USLS and SSLF groups respectively (p= 0.654), and those outcomes were excessive bleeding, bladder perforation (intraoperative) or gluteal pain, and urinary infection (postoperative), among others, without differences between the groups. Conclusion High cure rates in all compartments were observed according to the anatomical criterion (stage I), without differences in P-QoL scores and complications either with USLS or SSLF for the surgical treatment of accentuated POP.